Qualitative Teaching and Learning Needs Assessment for a Community of Academic Librarians. Issue 4 (18th May 2016) - Miller, Sara D.; Minkin, Rachel M.
ASBTRACT: The Information Literacy Unit at Michigan State University Libraries is tasked with providing teaching and learning support to 70+ librarian colleagues at MSU. The unit was asked to conduct a needs assessment to determine supportive needs, attitudes toward teaching and learning, and to lay groundwork for expanding the ability of the unit to provide support through building trust and strengthening relationships with librarian colleagues. An interview-based method grounded in social sciences rather than an assessment with a management focus was employed to accomplish these diverse tasks, which yielded actionable insights.